Dạy học khám phá khái niệm nội dung “Một số yếu tố xác suất” ở trung học cơ sở với sự hỗ trợ của trí tuệ nhân tạo - Nguyễn Viết Dương, Nguyễn Viết Dương; Nguyễn Thị Nga, Nguyễn Thị Nga (Tạp chí Giáo dục, 2026)
In the context of the increasing application of artificial intelligence (AI) in education, discovery-based concept learning has undergone significant changes compared with traditional approaches. However, the integration of AI into discovery-based instruction on probability topics at the lower secondary level remains underexplored. This paper aims to clarify how to organize discovery-based concept learning for the topic “Some Elements of Probability” with the support of AI. Drawing on theoretical research and analytical methods, the paper identifies relevant perspectives, classifications, and procedures for implementing discovery-based concept learning in an AIsupported environment. The findings provide practical orientations and suggestions while broadening the discussion on the potential to enhance the quality of teaching the topic “Some elements of probability” at the lower secondary level through the integration of AI.